Male to female birth ratios over a 35-year period - Hrvoje Vraneš; Hrvojka Soljačić Vraneš; Ivka Djaković; Vesna Gall; Ana Meyra Potkonjak (Medicinski glasnik, 2021)
Aim: Along with changes to the human physique recorded over the past decades in certain countries, there are also changes concerning the male-female birth ratio. The aim of this study was to establish the movement of male-female birth ratios and factors affecting the ratio. Methods: This retrospective study was conducted in Zagreb, Croatia, in the period from 1985 to 2019 on a sample of 3804 newborns. Results: In the 35-year period the ratio of boys and girls at birth did not change significantly. Girls had lower birth weight, and boys had higher birth length. In the war period (1992-1994), a mild increase in the ratio of boys was noted, but not statistically significant. Father’s age in the last period examined (2007-2009) showed to be a statistically significant predictor of the child’s gender. Namely, the descendants of younger fathers were statistically significantly more frequently girls, while the descendants of older fathers were more frequently boys. Married mothers had higher percentage of male births (51.5%), and a lower percentage (47.1%) by unmarried mothers. Conclusion: The changes in birth ratios are particularly pronounced in different age and socioeconomic groups of parents nowadays when the growth of living standards is accompanied by significant changes of the human physique.
Keywords: Croatia; gender; human body; newborn; parturition